PENGARUH KESADARAN MEMBAYAR PAJAK DAN PEMAHAMAN TENTANG PERPAJAKAN TERHADAP MINAT MEMBAYAR PAJAK PADA WAJIB PAJAK ORANG PRIBADI - Ainul Yusna Harahap; Nurliza Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
This study aims to determine the effect of tax awareness and understanding of taxation on interest in paying taxes on individual taxpayers in Langsa City. The population used in this study was 100 personal taxpayers registered at KPP Kota Langsa, with non-employee criteria registered at the Langsa City Tax Service Office and randomly selected. The tests carried out in data analysis are instrument validity and reliability tests, classical acceptance tests in the form of normality tests, multicollinearity tests, and heteroscedasticity tests. In this case, the hypothesis tests used are determination coefficient tests, regression tests, and multiple linear regression tests. The data collection method uses questionnaires processed with SPSS version 23. The results of this study are the results of multiple linear regression equations, it is known that awareness of paying taxes and understanding taxation have a positive influence on interest in paying taxes in Langsa City. The results of the T-test, it is known that the awareness of paying taxes and understanding of taxation has a significant partial effect on the interest in paying taxes in Langsa City. The results of the coefficient of determination test are known that the awareness of paying taxes and understanding of taxation is 60% of the interest in paying taxes. While the remaining 36.1% was influenced by other variables that were not studied in this study.